Integrin cytoplasmic domain-associated protein-1 attenuates sprouting angiogenesis - Brütsch, René Michael; Liebler, Sven Stefan; Wüstehube-Lausch, Joycelyn; Bartol, Arne; Herberich, Stefanie E.; Adam, M. Gordian; Telzerow, Anja; Augustin, Hellmut; Fischer, Andreas (Circulation research, 2010)
Rationale: - - The ICAP1 (integrin cytoplasmic domain-associated protein-1) is a specific intracellular binding protein of β1-integrins and the cerebral cavernous malformation (CCM) protein CCM1. ICAP1 recruits CCM1 to the cell membrane and activates CCM1 by changing its conformation. Because CCM1 plays a critical role for cardiovascular development, we hypothesized that its activator ICAP1 is involved in vascular differentiation. - - Objective: - - The objective of this study was to define the role of ICAP1 in endothelial cells. - - Methods and Results: - - Loss of ICAP1 in primary human endothelial cells causes excessive angiogenic branching and network formation in vitro (3D sprouting angiogenesis) and in vivo (xenotransplantation of ICAP1-silenced human endothelial cells). ICAP1 increases cell motility and the initial formation of capillary sprouts but prevents vessel outgrowth. ICAP1 inhibits Rho kinase activity and ERK (extracellular signal-regulated kinase) phosphorylation and induces expression of the cell cycle inhibitors p21 and p27, leading to less endothelial proliferation. However, ICAP1 promotes endothelial survival and AKT phosphorylation. Global gene expression analyses revealed that the ICAP1 effects are mediated by strong activation of DELTA-NOTCH signaling. Active NOTCH1 or silencing of the NOTCH ligand DLL4 phenocopy the ICAP1 effects and blockade of NOTCH cleavage rescues the ICAP1-mediated defects in endothelial cells. Both ICAP1 and NOTCH1 reduce the expression of ESM1 (endothelial cell-specific molecule-1), and silencing of ESM1 disturbs vascular endothelial growth factor- or fibroblast growth factor 2-induced sprouting angiogenesis. - - Conclusions: - - In this study, we identified ICAP1 as a novel regulator to prevent excessive sprouting angiogenesis.
Gesehen am 08.03.2023